(untitled) (Journal of Applied Oral Science, 2011)
OBJECTIVE: The aim of this study was to compare the polimerization ability of three different light-curing units (quartz tungsten halogen, light-emitting diodes and plasma arc) and their exposure modes (high-intensity and soft-start) by determination of microhardness, water sorption and solubility, and diametral tensile strength of 5 dual-curing resin cements. Material and methods: A total of 720 disc-shaped samples (1 mm height and 5 mm diameter) were prepared from different dual-curing resin cements (Duolink, Nexus, Bifix-QM, Panavia F and RelyX Unicem). Photoactivation was performed by using quartz tungsten halogen (high-power and soft-up modes), light-emitting diode (standard and exponential modes) and plasma arc (normal and ramp-curing modes) curing units through ceramic discs. Then the samples (n=8/per group) were stored dry in the dark at 37°C for 24 h. The Vickers hardness test was performed on the resin cement layer with a microhardness tester (Shimadzu HMV). For sorption and solubility tests; the samples were stored in a desiccator at 37°C and weighed to a constant mass. The samples were weighed both before and after being immersed in deionized water for different periods of time (24 h and 7 days) and being desiccated. The diametral tensile strength of the samples was tested in a universal testing machine at a crosshead speed of 0.5 mm/min. Data were analyzed statistically by nonparametric Kruskal Wallis and Mann-Whitney U tests at 5% significance level. RESULTS: Resin cement and light-curing unit had significant effects (p